Secrets of next-level entrepreneurs : 11 powerful lessons to thrive in business and lead a balanced life - Brueckmann, Alex (Hoboken, New Jersey : John Wiley & Sons, Inc., 2023)
"There are three mission-critical pillars that contribute to building future-proof businesses: strategy, leadership, and self-care. It?s essential to strategically re-adjust a business for success, consciously shape leadership and culture, and practice self-care as we humbly accept our own limitations as entrepreneurs. Instead of celebrating the hustle culture, promoting a glamorous view of entrepreneurship, or glorifying the few that amassed incredible wealth, this book is about, what Brueckmann calls, Next Level Entrepreneurship. It?s about building businesses that take the right steps to do well, be profitable, and contribute to building more equitable communities. It is for entrepreneurs and leaders who embrace their responsibility for social and environmental justice, contributing to a world that is worth living in?for us, our children, and generations to come. This book holds specific advice on issues that are on the mind of every business owner and leader at one point or another. Brueckmann and fellow contributors invite some of the brightest minds to contribute their perspectives on Next Level Entrepreneurship. We shed light on a range of interconnected topics that are critical success factors in today?s business world. This is not a theoretical textbook. Instead, we offer actionable solutions that you can put into practice right away?written from business owners and leaders for business owners and leaders"--
Includes bibliographical references.
Keywords: Entrepreneurship; Leadership; Strategic planning; Success in business